2016
DOI: 10.1128/jvi.00170-16
|View full text |Cite
|
Sign up to set email alerts
|

BPIFB6 Regulates Secretory Pathway Trafficking and Enterovirus Replication

Abstract: Bactericidal/permeability-increasing protein (BPI) fold-containing family B, member 3 (BPIFB3) is an endoplasmic reticulum (ER)-localized host factor that negatively regulates coxsackievirus B (CVB) replication through its control of the autophagic pathway. Here, we show that another member of the BPIFB family, BPIFB6, functions as a positive regulator of CVB, and other enterovirus, replication by controlling secretory pathway trafficking and Golgi complex morphology. We show that similar to BPIFB3, BPIFB6 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 44 publications
0
52
2
Order By: Relevance
“…Although little is known about LCN9, a related protein, neutrophil gelatinase-associated lipocalin, NGAL, has been associated with bacterial infection in humans [47][48][49]. BPiFB2 belongs to a family of proteins considered as a key component of the innate immune response against Gram-negative bacteria [50], but the physiological functions of the BPIFB family still remain largely unknown [51]. Despite this, a previous study on BPIFB2 has reported the involvement of BPIFB proteins regulating enterovirus infection, with BPIFB6 assisting the enterovirus replication by controlling secretory pathway trafficking and Golgi complex morphology [51].…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about LCN9, a related protein, neutrophil gelatinase-associated lipocalin, NGAL, has been associated with bacterial infection in humans [47][48][49]. BPiFB2 belongs to a family of proteins considered as a key component of the innate immune response against Gram-negative bacteria [50], but the physiological functions of the BPIFB family still remain largely unknown [51]. Despite this, a previous study on BPIFB2 has reported the involvement of BPIFB proteins regulating enterovirus infection, with BPIFB6 assisting the enterovirus replication by controlling secretory pathway trafficking and Golgi complex morphology [51].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression was determined based on a ΔC Q method (C Q is the Bio-Rad standard for cycle at point of quantification and is equivalent to C T ), normalized to the sample's C Q for human actin. Primer sequences for actin, MUC17, NAALADL1, CVB, E11, and EV71 have been previously described (17,18). All primer sequences used in the study are located in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were performed with CVB3 (RD), EV-71 (GDV083), or E11 (Gregory) that were expanded as described previously (17). For enteroid infections, wells (containing ∼100 enteroids) were infected with 10 6 pfu of the indicated virus.…”
Section: Methodsmentioning
confidence: 99%
“…We showed previously that BPIFB3 localizes to domains enriched for the ER sheet marker 156 CLIMP63 (26). Therefore, we sought to examine whether BPIFB3 is involved in regulating ER 157 morphology or turnover during flavivirus infection.…”
Section: Infection Of Bpifb3 Depleted Cells Induces Aberrant Er Strucmentioning
confidence: 99%
“…Despite the high degree of predicted structural 342 homology, BPIFB3 localizes to the ER and is not secreted (23). Of the other members of the 343 family, BPIFB2 and BPIFB6 are also ER localized, however neither appear to regulate autophagy 344 (26) (26). Of the related proteins, BPIFB6 is the only protein to 348 be characterized, and has been demonstrated to regulate secretory trafficking and Golgi 349 morphology (26).…”
mentioning
confidence: 99%